Ars critica numaria Joseph Eckhel (1737-1798) and the Transformation of Ancient Numismatics - Woytek, Bernhard; Williams, Daniela (2022)
This richly illustrated volume explores the life and work of the Austrian classical scholar Joseph Eckhel, a crucial figure in the transformation of numismatic studies into a modern discipline. It contains twenty-one essays by an interdisciplinary group of international authors examining various aspects of Eckhel's biography and scholarly activities: his Jesuit background, his formative study trip to Italy in 1773, his work as director of the imperial collection of ancient coins and professor of numismatics at the university of Vienna (from 1774), and especially his most important publications on ancient coins as well as on gems and cameos. Furthermore, the new book considers Eckhel's impact on contemporaries and later generations, with special regard to his role in the development of numismatic methodology in the Enlightenment and beyond.